1995
DOI: 10.1002/yea.320110503
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of carbon metabolism in chemostat cultures of Saccharomyces cerevisiae grown on mixtures of glucose and ethanol

Abstract: Growth efficiency and regulation of key enzyme activities were studied in carbon- and energy-limited chemostat cultures of Saccharomyces cerevisiae grown on mixtures of glucose and ethanol at a fixed dilution rate. Biomass yields on substrate carbon and oxygen could be adequately described as the net result of growth on the single substrates. Activities of isocitrate lyase and malate synthase were not detected in cell-free extracts of glucose-limited cultures. However, both enzymes were present when the ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 34 publications
8
104
0
Order By: Relevance
“…It was observed that, for the above inducible enzymes, clear predictions were made on their need as function of increasing ethanol fraction. This approach predicted: l The ethanol/glucose feed ratio where a particular enzyme started to be induced l The enzyme amount then increased linear with increasing ethanol fraction These predictions were qualitatively, but more surprising also quantitatively, validated using the wild type yeast [13,14]. Later additional validation was performed with null-mutants in the above enzymes, leading to a predicted maximal ethanol uptake rate of each mutant.…”
Section: Prediction Of Gene Regulation Of Enzymes Using Energy Optimamentioning
confidence: 77%
“…It was observed that, for the above inducible enzymes, clear predictions were made on their need as function of increasing ethanol fraction. This approach predicted: l The ethanol/glucose feed ratio where a particular enzyme started to be induced l The enzyme amount then increased linear with increasing ethanol fraction These predictions were qualitatively, but more surprising also quantitatively, validated using the wild type yeast [13,14]. Later additional validation was performed with null-mutants in the above enzymes, leading to a predicted maximal ethanol uptake rate of each mutant.…”
Section: Prediction Of Gene Regulation Of Enzymes Using Energy Optimamentioning
confidence: 77%
“…The biggest increase in production was observed when ethanol was added to the feed, initially as a glucose/ethanol mixed feed following the glucose batch phase of growth. The rationale for adding ethanol to the feed was that direct supply of ethanol may increase the supply of cytosolic acetyl-CoA to the mevalonate pathway (30). An alternative explanation is that use of ethanol eliminated glucose repression, but this scenario is considered unlikely as glucose was still present in the feed, and the concentration of glucose in the feed stage of the fed-batch fermentations was very low, and mostly undetectable.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction was started with 2 mM fructose 6-phosphate. Phosphofructokinase (PFK; EC 2.7.1.11) was assayed according to de Jong-Gubbels et al (1995), with minor modifications. The assay mixture contained: imidazole/ HCl (pH 7?0) 50 mM, MgCl 2 5 mM, NADH 0?15 mM, fructose 2,6-diphosphate 0?10 mM, fructose-1,6-diphosphate aldolase (FBA; Roche) 0?45 U ml 21 , glycerol-3-phosphate dehydrogenase (Roche) 0?6 U ml 21 , triosephosphate isomerase (TPI) 1?8 U ml 21 (Roche) and cell extract.…”
Section: Samples Of Cellsmentioning
confidence: 99%
“…Enolase (ENO; EC 4.2.1.11) was assayed according to van Hoek (2000). Pyruvate kinase (PYK; EC 2.7.1.40) was assayed according to de Jong-Gubbels et al (1995), with minor modifications. The assay mixture contained the following: cacodylic acid/KOH (pH 6?2) 100 mM, KCl 100 mM, ADP 10 mM, fructose 1,6-diphosphate 1 mM, MgCl 2 25 mM, NADH 0?15 mM, lactate dehydrogenase (Roche) 11?25 U ml 21 and cell extract.…”
Section: Samples Of Cellsmentioning
confidence: 99%